Transcriptional Reprogramming at Genome-Scale of Lactobacillus plantarum WCFS1 in Response to Olive Oil Challenge - Esteban-Torres, María; Reverón, Inés; Plaza-Vinuesa, Laura; de las Rivas, Blanca; Muñoz, Rosario; López de Felipe, Félix (Frontiers in Microbiology, 2017)
Dietary fats may exert selective pressures on Lactobacillus species, however knowledge on the mechanisms of adaptation to fat stress in these organisms is still fragmentary. This study was undertaken to gain insight into the mechanisms of adaptation of Lactobacillus plantarum WCFS1 to olive oil challenge by whole genome transcriptional profiling using DNA microarrays. A set of 230 genes were differentially expressed by L. plantarum WCFS1 to respond to this vegetable oil. This response involved elements typical of the stringent response, as indicated by the induction of genes involved in stress-related pathways and downregulation of genes related to processes associated with rapid growth. A set of genes involved in the transport and metabolism of compatible solutes were downregulated, indicating that this organism does not require osmoprotective mechanisms in presence of olive oil. The fatty acid biosynthetic pathway was thoroughly downregulated at the transcriptional level, which coincided with a diminished expression of genes controlled by this pathway in other organisms and that are required for the respiratory function, pyruvate dehydrogenase activity, RNA processing and cell size setting. Finally, a set of genes involved in host-cell signaling by L. plantarum were differentially regulated indicating that olive oil can influence the expression of metabolic traits involved in the crosstalk between this bacterium and the host.